Lymphocyte immunotherapy performed is pregnant gilts and sows did not affect preweaning mortality in the corresponding litters. - Maldonado, J G; González, M S; Otero, A M (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary This study was designed to test if lymphocyte immunotherapy (LI) of pregnant gilts and sows could improve preweaning mortality rates. In a commercial farm, Gilts (n = 61) first (n = 57) or second parity sows (n = 42) were selected and random assigned to treatment with saline (control group) or LI with lymphocytes obtained from multiparous sows, Boar, or growth-fattening pigs donors (alloimmunized groups). Treatments were performed at day 85 of pregnancy. Litter size and weight were evaluated by multifactor analysis of variance, whereas farrowing and preweaning mortality rates were analyzed by Mann-Whitney test. All traits evaluated at farrowing and at weaning did not significantly differ between groups (p > 0.05); when data from all immunized groups were altogether compared with control group (p > 0.5). Enteritis tended to be the most common cause of morbidity (p = 0.53). Mortality rate tended to increase in piglets from alloimmunized females (p = 0.12). The results suggest that LI of pregnant cross-bred gilts, first or second-parity sows did not affect preweaning mortality in piglets from subsequent lactation. Keywords: farrowing, litter size, litter weight, mortality, swine, weaning. Resumen El presente estudio se diseñó para evaluar si la terapia con linfocitos alogénicos (LI) aplicada en cerdas gestantes podía reducir las tasas de mortalidad en lactancia de sus respectivas camadas. En una granja porcícola comercial se seleccionaron cerdas gestantes (80-90 días) de primera (n = 61), segunda (n = 42) gestación, y se asignaron al azar al tratamiento con 1) linfocitos alogénicos (grupos inmunizados) obtenidos de cerdas gestantes, machos reproductores o cerdos de engorde; o 2) con solución salina (grupo control). Los datos del tamaño y el peso de la camada al nacer y al destete se registraron y evaluaron por análisis de varianza multifactorial mientras que la mortalidad al nacer y en la lactancia se evaluaron por prueba de Mann-Whitney. Ninguno de los parámetros evaluados de la camada al nacer y al destete, presentaron diferencias estadísticamente significativas entre los grupos aloinmunizados y el grupo control (p > 0,05). La enteritis mostro tendencia a ser mayor causa de mortalidad en lactancia (p = 0,053). La mortalidad presento tendencia a ser mayor en los lechones de las cerdas aloinmunizadas (p = 0,12). Los resultados sugieren que la terapia con linfocitos alogénicos, administrada en cerdas gestante de primera, segunda o tercera gestación, no afecta la mortalidad predestete de la subsecuente camada.